Integrated Marketing Communication in Building the Brand Image of Local Coffee Shops: A Systematic Literature Review, 2020–2025 - Yudha Yustiasa; Naomi Karina Hutagalung (Majapahit Journal of Islamic Finance and Management, 2026)
The rapid growth of digital technology has transformed how organizations communicate with consumers, making Integrated Marketing Communication (IMC) an important strategy for delivering consistent brand messages. In the competitive coffee shop industry, IMC is expected to strengthen Brand Image; however, previous studies have produced inconsistent findings regarding this relationship. This study aims to synthesize existing research on the influence of IMC on Brand Image in the coffee shop industry. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant articles were identified from several academic databases using predefined inclusion criteria, resulting in 20 eligible studies for analysis. The findings indicate that IMC strengthens Brand Image through consistent communication, integration of communication channels, increased Brand Awareness, Customer Engagement, and improved customer experience. However, IMC implementation in coffee shops remains focused primarily on social media and digital marketing, with limited integration of other communication elements. The review also identifies research gaps in study contexts, methodologies, and conceptual frameworks, providing recommendations for future research while offering practical insights for developing sustainable Brand Image strategies.